2019
DOI: 10.3389/fneur.2019.00387
|View full text |Cite
|
Sign up to set email alerts
|

Functional Head Impulse Test in Professional Athletes: Sport-Specific Normative Values and Implication for Sport-Related Concussion

Abstract: Dizziness, slow visual tracking, or blurred vision following active head (or body) movements are among the most common symptoms reported following sport-related concussion, often related to concurrent dysfunctions of the vestibular system. In some cases, symptoms persist even if bedside and auxiliary standard vestibular tests are unremarkable. New functional tests have been developed in recent years to objectify neurological alterations that are not captured by standard tests. The functional head impulse test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…In the study by Romano et al ., which determined the functional head impulse test normative values specific to different types of sport in the horizontal and vertical semicircular canal planes, the results for professional athletes and healthy non-athletes were compared. 9 There was no significant difference between the two groups in terms of the total percentage of correct answers, which was above 90 per cent for both groups. Accordingly, this study reported that a typical healthy individual is expected to give nearly 100 per cent of correct answers in the functional head impulse test.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In the study by Romano et al ., which determined the functional head impulse test normative values specific to different types of sport in the horizontal and vertical semicircular canal planes, the results for professional athletes and healthy non-athletes were compared. 9 There was no significant difference between the two groups in terms of the total percentage of correct answers, which was above 90 per cent for both groups. Accordingly, this study reported that a typical healthy individual is expected to give nearly 100 per cent of correct answers in the functional head impulse test.…”
Section: Discussionmentioning
confidence: 73%
“…A graphical user interface reports the number of impulses performed per acceleration step and the corresponding percentage of correct answers, thus helping the clinician to decide the head impulse acceleration rate. 1 , 9
Figure 1. Functional head impulse test results of the right and left lateral semicircular canals of a healthy participant.
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This test, commercialized by BeOnSolutions society ( ), is based on the ability of a subject to read an optotype briefly presented during impulsive head rotations at varying angular accelerations [ 26 ]. Several studies have been conducted already using this test in adults from the general population [ 15 , 27 ] or with vestibular neuritis [ 16 , 28 ]. Briefly, the testing procedure was as follows: the child was seated on a chair placed at 150 cm distance from a computer screen connected to the fHIT device ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the functional head impulse test (fHIT) was introduced among other laboratory vestibular tests (7)(8)(9)(10). Since fHIT is a subjective functional test and does not require analysis of eye movements as does vHIT, it also investigates the performance of the vestibular ocular reflex at a higher level in the brain (vestibular/associative cortex).…”
Section: Introductionmentioning
confidence: 99%